Implementation and Control of an AC/DC/AC Converter for Double Wound Flywheel Application. (22nd May 2012) - Oliveira, J. G.; Schettino, H.; Gama, V.; Carvalho, R.; Bernhoff, H.
Abstract : An all-electric driveline based on a double wound flywheel, connected in series between main energy storage and a wheel motor, is presented. The flywheel works as a power buffer, allowing the battery to deliver optimized power. It also separates electrically the system in two sides, with the battery connected to the low voltage side and the wheel motor connected to the high voltage side. This paper presents the implementation and control of the AC/DC/AC converter, used to connect the flywheel high voltage windings to the wheel motor. The converter general operation and the adopted control strategy are discussed. The implementation of the AC/DC/AC converter has been described from a practical perspective. Results from experimental tests performed in the full-system prototype are presented. The prototype system is running with satisfactory stability during acceleration mode. Good efficiency and unity power factor could be achieved, based on vector control and space vector modulation.